Changes in knowledge and awareness for a community-based cancer screening educational program - Shenghui Wu; Patricia Chalela; Amelie G Ramirez (BMC, 2023)
Abstract Background Cervical cancer (CC), colorectal cancer (CRC), and breast cancer (BC) are diseases that can be prevented/detected through early test. Through educational programs, individuals can become better informed about these cancers and understand the importance of screening and early detection. However, many people, especially low-income, low-educated, uninsured minority population groups, do not have their cancer screenings at the recommended intervals and do not receive appropriate and timely follow-up of abnormal screening results or timely treatment after diagnosis. A community-based educational program was developed to improve knowledge and awareness toward the screening of the three cancer types in a South Texas underserved population. Methods Residents living in Laredo, Texas were invited to participate in the present educational program. From January 2020 to April 2021, participants were recruited using social media and flyer distributions in the general community. Participants received a free live web cancer education presentation delivered by bilingual community health educators, and online pre- and post-education surveys for CC, CRC, and BC separately. Pre-post changes in knowledge for individual items were compared using McNemar's chi-squared tests. Results Overall, the participants showed increases in CC (n = 237), CRC (n = 59), and BC (n = 56) screening knowledge and awareness after receiving the cancer screening education (Ps < 0.05). After receiving the cancer screening education, 85-97% of participants had an intent to talk to a healthcare provider about CC/CRC/BC screening, 88-97% had an intent to get a CC/CRC/BC screening test in the next 12 months or at the next routine appointment, and 90-97% had an intent to talk about CC/CRC/BC with their family members or friends. Conclusions A community-based educational program culturally and linguistically tailored help increase knowledge and awareness about cervical, colorectal, and breast cancer screening, and promote positive changes in population's knowledge and awareness about the benefits of cancer screening. Future cancer screening educational programs in similar populations are warranted to reduce the risk of cervical, colorectal, and breast cancer.